Assessing readiness for the implementation of knowledge management in local governments : the case of Stellenbosch Municipality - Gaffoor, Shamin (Stellenbosch : Stellenbosch University, 2008)
Thesis (MComm (School of Public Management and Planning))--Stellenbosch University, 2008.